2013
DOI: 10.1016/j.jpeds.2013.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Haemophilus influenzae Type b Conjugate Vaccine on Radiologically-Confirmed Pneumonia in Young Children in Pakistan

Abstract: Objective The effectiveness of Haemophilus influenzae type b (Hib) vaccine in preventing severe pneumonia in Asian children has been questioned, and many large Asian countries yet to introduce Hib conjugate vaccine in immunization programs. The primary objective of this study was to assess Hib conjugate vaccine effectiveness (VE) on radiologically-confirmed pneumonia in children born after introduction of Hib conjugate vaccine in Pakistan. Study design A matched case-control study enrolled cases of radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The longevity of population level benefits might be shortened by serotype replacement occurring rapidly after vaccine introduction (as seen with seven-valent pneumococcal conjugate vaccines),130132 and by subsequent increases in non-vaccine-serotype pneumonia. H influenzae type b vaccines reduce pneumonia burden in low-income countries,133 and some evidence also supports a herd effect 134. However, vaccination will not affect the burden of colonisation with non-typable (not type b) H influenzae , which is substantially more common in developing countries than is H influenzae type b135 and has long been recognised as an important cause of pneumonia 127,136.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…The longevity of population level benefits might be shortened by serotype replacement occurring rapidly after vaccine introduction (as seen with seven-valent pneumococcal conjugate vaccines),130132 and by subsequent increases in non-vaccine-serotype pneumonia. H influenzae type b vaccines reduce pneumonia burden in low-income countries,133 and some evidence also supports a herd effect 134. However, vaccination will not affect the burden of colonisation with non-typable (not type b) H influenzae , which is substantially more common in developing countries than is H influenzae type b135 and has long been recognised as an important cause of pneumonia 127,136.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…15 The report from the surveillance network established in the WHO Eastern Mediterranean region 16 specifically addresses the benefits of conducting such surveillance using standardized protocols, but also the practical and field challenges of coordinating a surveillance network, especially as many regions face political instability and have difficulties transferring specimens and supplies across borders. It remains difficult to explain the high estimates of vaccine effectiveness reported through case-control studies, as seen in this supplement in Ukraine 17 and Pakistan, 18 and as was observed earlier in Bangladesh. 19 Various reasons related to study design and control selection have been proposed and efforts are currently ongoing to systematically avoid such biases in future studies.…”
mentioning
confidence: 80%
“…To date most studies that were conducted in Asia reported effectiveness estimates from case-control designs rather than population based incidence impact. Vaccine effectiveness was estimated to be 31% (−9% to 57%) in Brazil, 55% (7-78%) in children receiving three vaccine doses in Colombia, 21% (5-35%) in Gambia, 22% (−7% to 43%) in Chile, 45% (18-63%) in Ukraine and 62% (47-73%) in Pakistan [14,[29][30][31][32]. All but Gambia and Chile were case control studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Asian countries have been slow to include Hib vaccination into their routine schedules, and China and Thailand have still not introduced the vaccine [12]. An increasing body of evidence has been emerging that Hib substantially contributes to the burden of disease in Asia [13][14][15][16][17] and that the incidence and mortality associated with Hib in Southeast Asia are in fact similar to levels observed in many other parts of the world, in particular in the Americas [1]. This includes recent findings from Vietnam [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation